Pendekatan Hotspot sebagai Upaya Penanganan Krisis Pengungsi di Yunani Tahun 2015-2016 - Indrayanti, Kadek Riana; Priadarsini, Ni Wayan Rainy; Putri, Penny Kurnia (Program Studi Hubungan Internasional FISIP Universitas Udayana, 2023)
This study aims to see how the implementation of the European Union hotspot by Greece in solve the refugee crisis. The refugee crisis has become a threat in European countries that will affect to regional security. Therefore, this study refers to the concept of policy and refugees and regional security theory. This research found that the hotspot implementation in Greece served to detect the purposes and intentions of refugees who wanted to go to Europe. If they were not eligible to stay in Europe, they would risk a return. Meanwhile, rcefugees who were said to be eligible to stay, would proceed to the relocation process to go to another European country. Thus, with these refugee screening, the regional security in Europe would be protected from the threat of the refugees arrivals in their countries by using Greece as a refugee screening platform because of Greece’s position as the main gateway for refugees to Europe.